Acute Hemodynamic Decompensation During Catheter Ablation of Scar-Related Ventricular Tachycardia: Incidence, Predictors, and Impact on Mortality. (February 2015) - Santangeli, Pasquale; Muser, Daniele; Zado, Erica S.; Magnani, Silvia; Khetpal, Sumun; Hutchinson, Mathew D.; Supple, Gregory; Frankel, David S.; Garcia, Fermin C.; Bala, Rupa; Riley, Michael P.; Lin, David; et al.
Abstract : Background—: The occurrence of periprocedural acute hemodynamic decompensation (AHD) in patients undergoing radiofrequency catheter ablation of scar-related ventricular tachycardia (VT) has not been previously investigated. Methods and Results—: We identified univariate predictors of periprocedural AHD in 193 consecutive patients undergoing radiofrequency catheter ablation of scar-related VT. AHD was defined as persistent hypotension despite vasopressors and requiring mechanical support or procedure discontinuation. AHD occurred in 22 (11%) patients. Compared with the rest of the population, patients with AHD were older (68.5±10.7 versus 61.6±15.0 years; P =0.037); had a higher prevalence of diabetes mellitus (36% versus 18%; P =0.045), ischemic cardiomyopathy (86% versus 52%; P =0.002), chronic obstructive pulmonary disease (41% versus 13%; P =0.001), and VT storm (77% versus 43%; P =0.002); had more severe heart failure (New York Heart Association class III/IV: 55% versus 15%, P <0.001; left ventricular ejection fraction: 26±10% versus 36±16%, P =0.003); and more often received periprocedural general anesthesia (59% versus 29%; P =0.004). At 21±7 months follow-up, the mortality rate was higher in the AHD group compared with the rest of the population (50% versus 11%, log-rank P <0.001). Conclusions—: AHD occurs in 11% of patients undergoing radiofrequency catheter ablation of scar-related VT and is associated with increased risk of mortality over follow-up. AHD may be predicted by clinical factors, including advanced age, ischemic cardiomyopathy, more severe heart failure status (New York Heart Association class III/IV, lower ejection fraction), associated comorbidities (diabetes mellitus and chronic obstructive pulmonary disease), presentation with VT storm, and use of general anesthesia. Abstract : Supplemental Digital Content is available in the text.